Monitoramento da resposta molecular aos inibidores de tirosino-quinase em pacientes com leucemia mieloide crônica - Villa, Bárbara (2019)
Chronic Myeloid Leukemia (CML) is associated with the chromosome Philadelphia. This abnormal chromosome forms the chimeric BCR-ABL1 gene, which is responsible for producing a protein with tyrosine kinase activity. Tyrosine kinase inhibitors drugs (ITKs) used in Brazil are imatinib mesylate (IM), dasatinib and nilotinib. The response to these tests can be rated at three levels: hematological, cytogenetic and molecular. This last one is more sensitive and evaluated with Reaction in Chain of Real Time Polimerase (RQ-PCR). The treatment aims at achieving the Major Molecular Response (MMR), whose ratio of bcr-abl1 chimeric transcript levels and endogenous control are less than or equal to 0.1%. European Leukemia Net (ELN) establishes guidelines for molecular responses according to the quantification of transcripts and the time of treatment with ITQs, classifying them as optimal response, alert and failure. According to the literature, it is known that approximately 15-25% of patients treated with MI do not reach optimal response. Due to the low number of studies that show how the molecular monitoring of CML in Brazil is we decided to evaluate the molecular response to treatment with the ITQs of CML patients treated in HUSM through RQ-PCR monitoring for quantification of transcripts of the BCR-ABL1 fusion gene. The analysis was did through the database of the Hematology-Oncology Service of the HUSM and the quantification of the transcripts and the mutation search in the ABL gene were performed in an external laboratory. 117 medical records were reviewed, of which 58.11% were male. The mean age at diagnosis was 48.1 years and 9.4% of the patients died. Six patients were analyzed separately for different characteristics of the others. Thus, of the 111 patients, 52.25% of the patients received exclusively MI, 42.30% reached MMR at 12 months and 73.40% had MMR at some point during IM treatment. 54.25% of the patients who exclusively used IM reached the MMR and maintained it to the end. Of the 47.74% that changed ITQ, 58.82% reached MMR shortly after the exchange and maintained this response to the end. Of the 19 (37.25%) patients who failed during the exchange, 14 went to the third line of therapy. Currently, 91.06% of patients who use IM are with MRM, as are 65.37% of patients using nilotinib and 58.81% of those who use dasatinib. Of the patients who were tested for mutation in the ABL gene, 40% had presence. According to the criteria of the EUROSKI study, five patients would be eligible to enter a study protocol for Treatment-Free Referral. We observed an improvement in monitoring over time, as well as good MMR results compared to the three ITQs currently used in HUSM. Our results are in agreement with the literature and the HUSM has been